Biomedical waste management rule and changes in the policy - Raghuvanshi, Vijay Pratap; Raghuvanshi, Shiv Pratap (International Journal Of Community Medicine And Public Health, 2022)
The amount of biomedical waste being generated in our country is increasing day by day. Biomedical waste if not handled properly can pollute the environment and can spread many harmful diseases. Health care workers in our country are still not fully aware about proper BMW handling and disposal, despite increasing global awareness on it. Biomedical waste management rules was first implemented in India on 20th July, 1998. Thereafter, the rules have undergone amendments in years 2003, 2011 and 2016. Latest biomedical waste management rules, 2016 and (amendment) rules, 2018, were simplification of BWM disposal as compared to 2018 rules. The objective of this study was to understand the difference and compare key points to be known by all health care workers and also clarification and inclusions in the rules.